Temporal distribution of anti-HIV serologic tests demand and positivity in a Municipal Central Laboratory: are there increased after Carnival? - Passos, Mauro Romero Leal; Júnior, Christóvão Damião; Salciarini, Remo Jogaib; Machado, Leonardo M.; Rosa, Joel Correa da; Barreto, Maria Claudia Uzeda; Salles, Roberto de Souza; Barreto, Nero Araújo; Ferreira, Dennis de Carvalho (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: HIV infection can lead to a progressive immunosuppression and result in an AIDS-related infections complex and other manifestations in affected individuals. Data from the AIDS 2012 Epidemiological Bulletin from 1980 to 2010 reported 241,662 deaths from AIDS in Brazil. Niterói, in Rio de Janeiro State, is a medium-sized city, of 500,000 inhabitants approximately and expressive socioeconomic and cultural indicators. Objective: To evaluate the relationship between seasonal demand and positivity of anti-HIV tests in the Miguelote Viana Public Health Central Laboratory located in Niterói. Methods: This is a temporal series analytical cross-sectional study. Anti-HIV tests demand, positivity and days worked by Miguelote Viana Public Health Central Laboratory were analyzed from a database for the period from 2005 to 2010. Data was then statistically evaluated through a temporal series and hypothesis testing on tendency and seasonality. Miguelote Viana Public Health Central Laboratory is a reference center for the dosage of viral load and CD4 levels for all public health units of Niterói; also attending to the population of cities in Metropolitan Region II. This is an innovative research, since articles that relate anti-HIV tests demand increase/decrease with the respective months of the year have not been found yet. As a result, we present graphs, tables and charts. Results: From January 2005 to December 2010, we have registered 64,505 serological tests for HIV, as follows: 17.44% (11,252) in 2005; 16.36% (10,557) in 2006; 17.81% (11,494) in 2007; 17.12% (11,046) in 2008; 16.20% (10,452) in 2009; and 15.04% (9,704) in 2010. In annual average, the days worked per month were as follows: 20 in 2005; 19.5 in 2006; 19.8 in 2007; 19.6 in 2008; 19.7 in 2009 and 19.3 in 2010. The monthly average of days worked in the six years studied was: 21 in Jan; 17.3 in February; 21.6 in March; 17.3 in April; 20 in May; 18.6 in June; 21.6 in July; 22 in August; 20.3 in September; 20.3 in October; 17.3 in November and 18.6 days in December. The annual average of positivity in absolute numbers was as follows: 42.6 in 2005; 44.0 in 2006; 38.3 in 2007; 32.8 in 2008; 24.25 in 2009 and 25.25 in 2010. The average positivity per month in the six years studied was the following: 39.3 in January; 29.3 in February; 40.8 in March; 31.8 in April; 31.1 in May; 34.6 in June; 33.8 in July; 38.6 in August; 35.0 in September; 34.8 in October; 31.5 in November and 33.6 in December. The average percentage of positivity per month was as follows: January (4.35), February (3.85), March (3.95), April (3.88), May (3.56), June (2.34), July (3.54), August (3.80), September (3.79), October (3.60), November (3.92) and December (3.75). In the studied period (2005-2010), Carnival holidays occurred in the month of February, on the following days: 8, 28, 20, 5, 24 and 16, respectively. Conclusion: We observed no seasonal relation between demand and positivity of anti-HIV tests carried out at Miguelote Viana Public Health Central Laboratory. A significant statistical decrease occurred in both anti-HIV tests demand and positivity during the studied years of the 2005–2010 series.